Bibliometric Analysis of the Development of Entrepreneurial Ecosystem Research in Global Publications - Loso Judijanto; Widyatmoko Widyatmoko (West Science Business and Management, 2024)
This study conducts a comprehensive bibliometric analysis of the field of entrepreneurial ecosystems, mapping the evolving landscape of research from 1995 to 2024. Utilizing VOSviewer for visual network analysis, the research identifies central themes, examines co-authorship and institutional collaboration networks, and highlights the temporal progression of key topics. The findings reveal "entrepreneurial ecosystem" as a nexus connecting diverse research themes such as innovation, economic growth, and sustainability. Significant emphasis is placed on the integration of digital technologies and sustainability within entrepreneurial practices, reflecting shifting academic and practical priorities. The analysis of co-authorship networks shows robust collaboration among leading scholars and institutions, predominantly from Western regions, with increasing contributions from a global cohort. The study underscores the importance of incorporating diverse perspectives to fully understand the multifaceted nature of entrepreneurial ecosystems and suggests future research directions focusing on digital transformation and sustainability in entrepreneurship.